2019
DOI: 10.1093/geront/gnz062
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Retirement on Cardiovascular Disease and Its Risk Factors: A Systematic Review of Longitudinal Studies

Abstract: Background and Objectives People are now spending longer in retirement than ever before and retirement has been found to influence health. This study systematically reviewed the impact of retirement on cardiovascular disease (CVD) and its risk factors (metabolic risk factors, blood biomarkers, physical activity, smoking, drinking, and diet). Research Design and Methods Longitudinal studies published in Medline, Embase, Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 88 publications
(138 reference statements)
3
55
3
1
Order By: Relevance
“…Our results in which women showed higher levels of MetSSS is in agreement with previous observations in which women showed a higher risk of CV mortality attributed to the higher prevalence of MetS in elderly women [29] and the distribution of central adiposity, insulin resistance, and hormonal regulation [30]. In accordance with our results showing that retired participants were less frequent in the highest MetSSS tertiles, previous observations have associated retirement with increasing LTPA [31]. Smoking is associated with MetS and its individual components, and smoking cessation is beneficial to MetS [32].…”
Section: Sociodemographic Factorssupporting
confidence: 93%
“…Our results in which women showed higher levels of MetSSS is in agreement with previous observations in which women showed a higher risk of CV mortality attributed to the higher prevalence of MetS in elderly women [29] and the distribution of central adiposity, insulin resistance, and hormonal regulation [30]. In accordance with our results showing that retired participants were less frequent in the highest MetSSS tertiles, previous observations have associated retirement with increasing LTPA [31]. Smoking is associated with MetS and its individual components, and smoking cessation is beneficial to MetS [32].…”
Section: Sociodemographic Factorssupporting
confidence: 93%
“…The present study showed, retired older adults have a higher risk of CVD after adjusted for age, sex and other socioeconomic characteristics. A recent systematic review indicated the impact of retirement on the rate of CVDs and risk factors varies across countries, in which studies in the European countries showed a detrimental effect of retirement on CVDs [ 44 ]. Pedron and colleagues identified male and low-educated retirees as potential high-risk groups for worsening CVD risk factors after retirement [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of retirement on physical health outcomes (in particular physical health indexes, CVD risk factors, hospitalizations, mortality, and self‐reported general health) is less clear, as both positive (Carrino, Glaser, and Avendano 2018; Coe and Zamarro 2011; Insler 2014), null (Dayaram and McGuire 2019; Hagen 2018; Hernaes et al 2013; Johnston and Lee 2009), and negative effects have been reported (Behncke 2012; Dave, Rashad, and Spasojevic 2008). Xue et al (2019) performed a systematic review of longitudinal studies on the impact of retirement on CVD and its risk factors and identified eighty‐two articles on the topic. Thanks to the very detailed synthesis of the papers included in their review, it was possible to discover that only sixteen of the eighty‐two studies adopted a causal design and only two of these focused on diagnosis of CVD as outcome, while the remaining analyzed the effect of retirement on adiposity measures, metabolic chronic conditions, healthy diet, physical activities, and smoking.…”
Section: The Health Effects Of Retirementmentioning
confidence: 99%
“…Surprisingly, the relationship between cardiovascular diseases and age at retirement is an understudied topic. As has emerged by a recent systematic review of the literature on the effect of retirement on cardiovascular diseases and its risk factors (Xue et al 2019), only two out of the eighty-two reviewed articles employed a causal design to study the impact of retirement on diagnosis of cardiovascular diseases (hereafter: CVD), while the effect of age at retirement on CVD has never been investigated. Most previous studies indeed looked at retirement rather than retirement age.…”
Section: Introductionmentioning
confidence: 99%